Identification of Occupational Safety and Health Hazards at Paint and Welding Workshop using the HIRARC Method - Amalia, Elma Nurul; Tianisa, Berliana Noor; Nursucilowati, Luvi Lia; Rizallihadi, M. Ditra; Mahartiko, Ardheta Heru; Sabriyanti, Firda Aliya; Febrianti, Aulia; Sanda, Delyanti Pare; Nizam, Muhammad Fakrul; Widowati, Evi; Sulistyani, Ummi Nur Laila (Journal of Safety Education, 2024)
Occupational Health and Safety (OHS) is important for every company to pay attention to. Preventing work accidents can be done by knowing the existing risks, one of which is through the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. Body Repair, Paint, and Welding Workshop "Family 99" is a small to medium-sized entrepreneurship that operates in car repair, paint, and welding services. The research aims to analyze the potential dangers found in the Body Repair, Paint and Welding Workshop "Family 99". Hazard identification was conducted in the workshop work area, with research respondents totaling three active workers. The data collection employed observation and interviews with a descriptive approach. According to the research results obtained from a total of 14 work stages analyzed, two stages had the highest risk value, namely the paint peeling stage with a risk value of 12, and the first, second, and third sanding stages with a risk value of 9. Controls that can be carried out to reduce risks include administrative controls and the use of Personal Protective Equipment (PPE) for workers to work safely and comfortably.